Impact of multicomponent integrated care on mortality and hospitalization after acute coronary syndrome: a systematic review and meta-analysis - Hoo, Jia-Xin; Yang, Ya-Feng; Tan, Jia-Yin; Yang, Jingli; Yang, Aimin; Lim, Lee-Ling (European heart journal. Quality of care & clinical outcomes, 2023)
Abstract Aims Multicomponent integrated care is associated with sustained control of multiple cardiometabolic risk factors among patients with type 2 diabetes. There is a lack of data in patients with acute coronary syndrome (ACS). We aimed to examine its efficacy on mortality and hospitalization outcomes among patients with ACS in outpatient settings. Methods and results A literature search was conducted on PubMed, EMBASE, Ovid, and Cochrane library databases for randomized controlled trials, published in English language between January 1980 and November 2020. Multicomponent integrated care defined as two or more quality improvement strategies targeting different domains (the healthcare system, healthcare providers, and patients) for one month or more. The study outcomes were all-cause and cardiovascular-related mortality, hospitalization, and emergency department visits. We pooled the risk ratio (RR) with 95% confidence interval (CI) for the association between multicomponent integrated care and study outcomes using the Mantel–Haenszel test. 74 trials (n = 93 278 patients with ACS) were eligible. The most common quality improvement strategies were team change (83.8%), patient education (62.2%), and facilitated patient-provider relay (54.1%). Compared with usual care, multicomponent integrated care was associated with reduced risks for all-cause mortality (RR 0.83, 95% CI 0.77–0.90; P < 0.001; I2 = 0%), cardiovascular mortality (RR 0.81, 95% CI 0.73–0.89; P < 0.001; I2 = 24%) and all-cause hospitalization (RR 0.88, 95 % CI, 0.78–0.99; P = 0.040; I2 = 58%). The associations of multicomponent integrated care with cardiovascular-related hospitalization, emergency department visits and unplanned outpatient visits were not statistically significant. Conclusion In outpatient settings, multicomponent integrated care can reduce risks for mortality and hospitalization in patients with ACS. Graphical Abstract Graphical Abstract Impact of multicomponent integrated care on mortality and hospitalization after acute coronary syndrome: a systematic review and meta-analysis.